2015
DOI: 10.1590/0037-8682-0120-2015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and antifungal susceptibility profiles of Candida parapsilosis complex species isolated from culture collection of clinical samples

Abstract: Introduction:Candida parapsilosis is a common yeast species found in cases of onychomycosis and candidemia associated with infected intravascular devices. In this study, we differentiated Candida parapsilosis sensu stricto, Candida orthopsilosis, and Candida metapsilosis from a culture collection containing blood and subungual scraping samples. Furthermore, we assessed the in vitro antifungal susceptibility of these species to fl uconazole, itraconazole, voriconazole, posaconazole, amphotericin B, and caspofun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
(47 reference statements)
2
9
1
Order By: Relevance
“…This result is in line with other studies [19,20]. However, Ataides F et al [14] and Lockhart et al, [6] reported C. parapsilosis sensu stricto species resistance to AMB. The response of the parapsilosis species complex to AMB varies considerably from one region to another, which could be determined by genotypic variability of the three species involved in this complex.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This result is in line with other studies [19,20]. However, Ataides F et al [14] and Lockhart et al, [6] reported C. parapsilosis sensu stricto species resistance to AMB. The response of the parapsilosis species complex to AMB varies considerably from one region to another, which could be determined by genotypic variability of the three species involved in this complex.…”
Section: Discussionsupporting
confidence: 89%
“…Candida parapsilosis is currently considered an emerging nosocomial pathogen [14], and its growing resistance to the azole and echinocandins groups [3,7,10,11] has placed it in the spotlight in recent years. It is an integrated complex composed of 3 species phenotypically indistinguishable, but due to its genetic heterogeneity, such discrimination is possible using molecular techniques only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the complex, C. parapsilosis sensu stricto is the most isolated species in clinical isolates derived from immunocompetent patients both pathological conditions and such commensal [6,7]. This is knowledge that has been supported by many studies worldwide.…”
Section: Discussionmentioning
confidence: 98%
“…Currently, Candida parapsilosisis considered as a nosocomial emerging pathogen [33][34][35][36], and its growing resistance to azoles and echinocandins [37][38][39] has put it under the spotlight in the last few years. It is a complex of 3 phenotypically indistinguishable species, but, due to their genetic heterogeneity, it is possible to differentiate them only with molecular techniques [40].…”
Section: Discussionmentioning
confidence: 99%